2005
DOI: 10.1126/science.1108329
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Dependent Cysteine Biosynthesis in Archaea

Abstract: Several methanogenic archaea lack cysteinyl-transfer RNA (tRNA) synthetase (CysRS), the essential enzyme that provides Cys-tRNA(Cys) for translation in most organisms. Partial purification of the corresponding activity from Methanocaldococcus jannaschii indicated that tRNA(Cys) becomes acylated with O-phosphoserine (Sep) but not with cysteine. Further analyses identified a class II-type O-phosphoseryl-tRNA synthetase (SepRS) and Sep-tRNA:Cys-tRNA synthase (SepCysS). SepRS specifically forms Sep-tRNA(Cys), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
286
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(293 citation statements)
references
References 30 publications
5
286
0
2
Order By: Relevance
“…MJ1660 and its orthologs form a monophyletic gene family that is obviously unrelated to the typical class I CysRS (9). The story was soon confirmed and elaborated by the elegant biochemical and genetic work of Söll and colleagues (10), who showed that the suspected class II CysRS, now properly renamed SepRS (O-phosphoseryl-RS), actually loaded O-phosphoserine (Sep), a precursor of cysteine, onto tRNA Cys . The noncognate Sep-tRNA Cys is then converted to the cognate pairing by the enzyme Sep-tRNA:Cys-tRNA synthase (SepCysS) (MJ1678).…”
mentioning
confidence: 56%
“…MJ1660 and its orthologs form a monophyletic gene family that is obviously unrelated to the typical class I CysRS (9). The story was soon confirmed and elaborated by the elegant biochemical and genetic work of Söll and colleagues (10), who showed that the suspected class II CysRS, now properly renamed SepRS (O-phosphoseryl-RS), actually loaded O-phosphoserine (Sep), a precursor of cysteine, onto tRNA Cys . The noncognate Sep-tRNA Cys is then converted to the cognate pairing by the enzyme Sep-tRNA:Cys-tRNA synthase (SepCysS) (MJ1678).…”
mentioning
confidence: 56%
“…For both Class I and Class II aminoacyl-tRNA synthetases, the pre-steady state kinetics of aminoacylation can be simplified using a two step irreversible mechanism: (7) For this mechanism, the time dependence of product formation is given by a single exponential followed by a linear phase: (8) In this form of the equation, [P] represents the concentration of product formed, and [E 0 ] represents the concentration of enzyme in the reaction. The quotient [P]/[E 0 ] is a useful way to express the moles of product formed per active site, and is thus independent of the amount of enzyme used in the experiment.…”
Section: Rapid Quench Methods For Studying the Half Reactions Of Aminmentioning
confidence: 99%
“…In some taxa, there is an aaRS corresponding to each of the 20 standard amino acids. However, only 17 canonical aaRS are conserved in all organisms: for asparagine, glutamine, and cysteine, indirect pathways exist by which the AA-tRNA AA is synthesized on the tRNA, after initial aminoacylation by a noncognate or noncanonical aaRS [7,8]. Each aaRS obligatorily interacts with three distinct substrates: ATP, amino acid and tRNA.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, O-phosphoseryl-tRNA synthetase (SepRS), a novel class II aaRS encoded by MJ1660, forms Sep-tRNA Cys . Then a second enzyme, Sep-tRNA:Cys-tRNA synthase (SepCysS), converts this tRNA to correctly charged Cys-tRNA Cys (27). This indirect mechanism of Cys-tRNA formation is confined to certain members of the Euryarchaea (Fig.…”
mentioning
confidence: 99%
“…An initial suggestion (25), later supported by bioinformatic analysis (26), predicted a class II tRNA synthetase (encoded by MJ1660) would cysteinylate tRNA Cys . However, biochemical work established that in M. jannaschii Cys-tRNA is formed by a two-step pretranslational amino acid modification (27). In the first step, O-phosphoseryl-tRNA synthetase (SepRS), a novel class II aaRS encoded by MJ1660, forms Sep-tRNA Cys .…”
mentioning
confidence: 99%